The right words at the right time - Thomas, Marlo (New York Atria Books, 2002)
"For everyone who needs a hero or loves a good story, here is an inspiring collection of personal revelations from more than 100 remarkable men and women who share a moment when words changed their lives"--Jacket.
David Mamet, Wilma Mankiller, Mary Matalin, Dave Matthews, John McCain, Paul McCartney, Dennis Miller, Toni Morrison, Ralph Nader, Willie Nelson, Paul Newman, Mice Nichols, Jack Nicholson, Conan O'Brien, Rosie O'Donnell, Shaquille O'Neal, Al Pacino, Gwyneth Paltrow, Sarah Jessica Parker, Sean Penn, Itzhak Perlman, Bob Pittman, Sidney Poitier, Vladimir Pozner, Anna Quindlen, Cal Ripken Jr., Dennis Rivers, Chris Rock, Ray Romano, Carlos Santana, Diane Sawyer, Martin Sheen, Ruth Simmons, Carly Simon, Sammy Sosa, Steven Spielberg, George Steinbrenner, Gloria Steinem, Marthha Stewart, Amy Tan, Julie Taymor, Twyla Tharp, Ted Turner, Mike Wallace, Vera Wang, Wendy Wasserstein, Maxine Waters, Venus Williams, Oprah Winfrey, Tom Wolfe, and the Dalai Lama.
"Marlo Thomas and friends have contributed their stories and royalties ... to St. Jude Children's Research Hospital"--Jacket.
UCWS-2014-G-1811 donated by Sandra Repulda Gonzales
Keywords: Success; Celebrities -- United States